Spectral performance of SKA log-periodic antennas I: Mitigating spectral artefacts in SKA1-LOW 21 cm cosmology experiments - de Lera Acedo, E.; Trott, Cathryn; Wayth, Randall; Fagnoni, N.; Bernardi, G.; Wakley, B.; Koopmans, L.; Faulkner, A.; bij de Vaate, J. (Oxford University Press, 2017)
This paper is the first in a series of papers describing the impact of antenna instrumental artefacts on the 21 cm cosmology experiments to be carried out by the low frequency instrument (SKA1-LOW) of the Square Kilometre Array telescope (SKA), i.e. the Cosmic Dawn (CD) and the Epoch of Reionization (EoR). The smoothness of the passband response of the current log-periodic antenna being developed for the SKA1-LOW is analysed using numerical electromagnetic simulations. The amplitude variations over the frequency range are characterized using low-order polynomials defined locally, in order to study the impact of the passband smoothness in the instrument calibration and CD/EoR Science. A solution is offered to correct a fast ripple found at 60 MHz during a test campaign at the SKA site at the Murchison Radioastronomy Observatory, Western Australia in 2015 September with a minor impact on the telescope's performance and design. A comparison with the Hydrogen Epoch of Reionization Array antenna is also shown demonstrating the potential use of the SKA1-LOW antenna for the delay-spectrum technique to detect the EoR.